Preparation, characterization and in vitro behavior of a new eutectoid bioceramic. Issue 1 (January 2015) - Rubio, V.; Mazón, P.; de la Casa-Lillo, M.A.; De Aza, P.N.
Abstract: A new type of bioceramic has been designed and obtained within the sub-system Ca2 SiO4 –7CaOP2 O5 2SiO2 . The selected composition was that corresponding to the eutectoid point 69 wt% dicalcium silicate–31 wt% tricalcium phosphate. Sintering behavior, phase evolution and microstructural changes were analyzed by XRD and SEM. Bio-reactivity was determined by immersion of materials in simulated body fluid for several periods of time as well as studies in human adipose stem cells (hASC). The investigated materials are bio-acceptable since no toxic or other harmful evidence was detected. A carbonated hydroxyapatite was formed on the surface of the 31R material within 3 days. Cell attachment assay showed that the ceramics supported the hASC cells adhesion and spreading, and the cells established close contacts with the ceramics after 24 h of culture. The influence of the microstructure (porosity, grain size and phase composition) on the in vitro behavior of the obtained bioceramics was also examined.